2013
DOI: 10.1007/s00264-013-2202-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle transfers in children and adults improve external rotation in cases of obstetrical brachial plexus paralysis: a comparative study

Abstract: This technique improves external rotation and abduction of the shoulder for daily living activities in children and young, skeletally mature, patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The procedure includes a surgical release of muscle contractures, tendon transfers, free-muscle transplantation and osteotomies. Surgery should be carried out after the age of 4 years when the child has ability to cooperate with rehabilitation and severe contractures are absent [15,6]. Although the present study contains a limited number of patients, our results demonstrate that improved function can be obtained for infants with obstetrical brachial plexus injury with early surgical reconstruction.…”
Section: Discussionmentioning
confidence: 47%
“…The procedure includes a surgical release of muscle contractures, tendon transfers, free-muscle transplantation and osteotomies. Surgery should be carried out after the age of 4 years when the child has ability to cooperate with rehabilitation and severe contractures are absent [15,6]. Although the present study contains a limited number of patients, our results demonstrate that improved function can be obtained for infants with obstetrical brachial plexus injury with early surgical reconstruction.…”
Section: Discussionmentioning
confidence: 47%
“…20,31,37,40,42 The mean external rotation improvement ranged between 12° to 72° in the soft-tissue release group, 20,27,31,32,37,42 and between 29° and 128° in the soft-tissue lengthening group. 28,30,33,35,39,43 Since the surgical techniques are different, the groups cannot be compared. One study found preferable results after subscapularis release combined with a latissimus dorsi transfer compared to subscapularis release only.…”
Section: Resultsmentioning
confidence: 99%
“…19 To evaluate the correlation of age at surgery and radiological and functional outcome, eight studies performed a subgroup analysis. 28,30,33,35,36,38-40 Jönsson et al 36 described an improvement of glenoid version in all age subgroups (0 to 2, 2 to 5, and > 5 years) without significant differences between the groups after a subscapularis lengthening at ten-year follow-up. Additionally, five other studies described no differences in functional outcome regarding external rotation and abduction between different age subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations